Speech genres and other late essays - Bakhtin, M. M. (Mikhail Mikhaĭlovich), 1895-1975 (University of Texas Press Slavic series ;, 1986)
"Speech Genres and Other Late Essays presents six short works from Bakhtin's Esthetics of Creative Discourse, published in Moscow in 1979. This is the last of Bakhtin's extant manuscripts published in the Soviet Union. All but one of these essays (the one on the Bildungsroman) were written in Bakhtin's later years and thus they bear the stamp of a thinker who has accumulated a huge storehouse of factual material, to which he has devoted a lifetime of analysis, reflection, and reconsideration."--Page 4 of cover